2017
DOI: 10.1103/physreve.96.053313
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the asymptotic states of modulated open quantum systems with a numerically exact realization of the quantum trajectory method

Abstract: Quantum systems out of equilibrium are presently a subject of active research, both in theoretical and experimental domains. In this work we consider time-periodically modulated quantum systems which are in contact with a stationary environment. Within the framework of a quantum master equation, the asymptotic states of such systems are described by time-periodic density operators. Resolution of these operators constitutes a non-trivial computational task. Approaches based on spectral and iterative methods are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In Refs. [75,76] we consider the problem of reaching the asymptotic state of a non-equilibrium open quantum model by using the QTalgorithm. We demonstrated that on a comparatively small cluster it is possible to propagate models with N = 2000 states.…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [75,76] we consider the problem of reaching the asymptotic state of a non-equilibrium open quantum model by using the QTalgorithm. We demonstrated that on a comparatively small cluster it is possible to propagate models with N = 2000 states.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the trajectories is calculated as the absolute difference between the two corresponding observables θ . We implement a high-performance realization of the quantum jumps method 27 to generate M r = 10 2 different trajectories for every considered set of model parameters. We first integrate each trajectory up to time t 0 = 10T in order to propagate the model system into the asymptotic regime, and then we follow the dynamics of fiducial and auxiliary trajectories up to time t = 10T .…”
Section: Methodsmentioning
confidence: 99%
“…(1) at time t p for the initial density matrix . We make use of the recently developed high-performance realization of the method 53 and generate different trajectories for averaging, leaving time for relaxation towards an asymptotic state, and following the dynamics for up to .…”
Section: Model and Methodsmentioning
confidence: 99%